Pemberdayaan Nelayan Pesisir Pantai Kenjeran oleh Dinas Ketahanan Pangan dan Pertanian Kota Surabaya dalam Pengembangan Kawasan Perikanan - Adhitya Yudha Satria, Adhitya Yudha Satria; Sri Wibawani, Sri Wibawani (Reslaj: Religion Education Social Laa Roiba Journal, 2024)
This study aims to examine the empowerment of Kenjeran coastal fishermen by the Surabaya City DKPP in developing fishery areas. The background of this writing is that several fishermen empowerment programs carried out by the City Government of Surabaya have not run optimally. This is further exacerbated by conditions of limited accessibility and other social tensions. This study refers to the theory of Mardikanto & Soebianto (2017:111-112) in which there are 9 (nine) indicators of community empowerment, namely 1) improving education, 2) improving accessibility, 3) improving actions, 4) institutional improvement, 5) business improvement, 6) income improvement, 7) environmental improvement, 8) life improvement, and 9) community improvement. This research method uses a qualitative descriptive method. Data obtained through observation, interviews, and documentation. The results of this study indicate that the empowerment that has been carried out by DKPP Kota Surabaya in developing regional fisheries in the empowerment process that has been carried out has been considered quite successful, being able to increase the catch of fishermen so that it is very helpful for fishermen and can improve the welfare of fishermen in general even though in practice there are still deficiencies.